PERANCANGAN SISTEM INFORMASI PERSEDIAAN BAHAN BAKU DI UD. XY, TULUNGAGUNG - Retno Astuti, Reza Ashari, dan Mas’ud Ef (Department of Agroindustrial Technology, Bogor Agricultural University, 2019)
The availability of raw material supplies is very important in maintaining the sustainability of the production process in a company. The purpose of this research was to design a web-based raw material inventory information system to meet the needs of users in controlling shanghai peanut raw material supplies. The system approach method used in this study was prototyping. System design used the concept of Object Oriented Programming (OOP) with UML version 2.0, MySQL and XAMPP databases as local servers and the PHP programming language. The result of the information were information about the list of raw materials, supply of raw materials, use of raw materials, and availability of raw materials for shanghai peanut in the warehouse. Verification and validation tests using the black box method and the system design test showed that the results of the information system design have been running well and as expectedKeywords: information system, inventory, peanut,raw materials